2017
DOI: 10.1073/pnas.1619416114
|View full text |Cite
|
Sign up to set email alerts
|

Biliary epithelial injury-induced regenerative response by IL-33 promotes cholangiocarcinogenesis from peribiliary glands

Abstract: The carcinogenic mechanism of extrahepatic cholangiocarcinoma (ECC) is unclear, due at least in part to the lack of an appropriate mouse model. Because human studies have reported frequent genetic alterations in the Ras-and TGFβ/SMAD-signaling pathways in ECC, mice with tamoxifen-inducible, duct-cell-specific Kras activation and a TGFβ receptor type 2 (TGFβR2) deletion were first generated by crossing LSL-Kras G12D , Tgfbr2 flox/flox , and K19 CreERT mice (KT-K19 CreERT ). However, KT-K19 CreERT mice showed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 44 publications
(48 reference statements)
2
100
0
Order By: Relevance
“…In PSC, BTSCs proliferate extensively, show few signs of cellular senescence, and have been proven to be able to escape immune response . A report based on lineage tracing in mice suggested that cells within PBGs could represent the origin of extrahepatic CCA, which supports our data in patients with PSC . In keeping with this, CCAs in patients with PSC diffusely expressed stem cell markers and primarily involved PBGs, which were largely substituted by neoplastic cells.…”
Section: Discussionsupporting
confidence: 90%
“…In PSC, BTSCs proliferate extensively, show few signs of cellular senescence, and have been proven to be able to escape immune response . A report based on lineage tracing in mice suggested that cells within PBGs could represent the origin of extrahepatic CCA, which supports our data in patients with PSC . In keeping with this, CCAs in patients with PSC diffusely expressed stem cell markers and primarily involved PBGs, which were largely substituted by neoplastic cells.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, KRAS mutations were slightly less common in IL‐33 high cases than in IL‐33 low cases. In an experimental model study, the administration of IL‐33 enhanced tumorigenesis of cancers with gene mutations that were insufficient for malignant transformation by themselves . A whole‐genome expression profiling study involving 149 iCCAs identified two subtypes with distinct molecular alterations .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin (IL)‐6 is regarded as a cytokine that is relevant to bile duct cancer development, because this inflammatory mediator, which is secreted by CCA cell lines, induces cell proliferation . Recent studies using transgenic mice also highlighted the pro‐oncogenic effects of IL‐33 on cholangiocytes . Although the combination of a Kras mutation and transforming growth factor‐β receptor type 2 gene ( Tgfbr2 ) deletion did not generate bile duct cancers, the additional administration of IL‐33 facilitated cancer development in the bile duct.…”
Section: Introductionmentioning
confidence: 99%
“…In general, ILC2s have been considered as a population with predominant pro-tumorigenic activity and the IL-33/ILC2/IL-13 circuit was shown to be critically involved in promoting cholangiocyte hyperplasia in murine cholangiocarcinoma [26] and in activating myeloid-derived suppressor cells, which inhibit anti-cancer immunity in breast cancer [27]. Interestingly, IL-33-activated ILC2s also express AREG early after tissue damage.…”
Section: Il-33 Ilc2s and Aregmentioning
confidence: 99%
“…In murine models of colitis [28] and infection-induced lung injury [29,30], AREG-expressing ILC2s were associated with restoration of epithelial integrity and tissue function. However, although early induction of AREG is important for the resolution of acute inflammation, the situation is quite different in the context of chronic inflammation where ILC2-derived AREG amplified excessive wound healing in skin lesions of atopic dermatitis patients [31] and triggered injury-induced regenerative responses driving development of extrahepatic cholangiocarcinoma [26].…”
Section: Il-33 Ilc2s and Aregmentioning
confidence: 99%